Perilaku Ibu tentang Makanan selama Masa Kehamilan untuk Mencegah Berat Bayi Lahir Rendah - Berman Fernando; Donald F. Sitompul; Dina Olivia Napitupulu (Universitas Methodist Indonesia, 2024)
Background : In developing countries, including indonesia, nutritional problems are still major public healt problem. Low nutritional status of pregnant women during pregnancy may result in various adverse effects for both mother and baby, among them are babies born with low birth weight.In pregnant women need to consume good food during pregnancy. The study aims to determine Mother’s behavior about food during pregnancy to prevent low birth weight in department obstetrics and gynecology Dr. Pirngadi Medan General Hospital on 2017 Methods : This is descriptive study with cross sectional design, the data were collected with questionnaires and analyzed with the SPSS (statistical product and service solutions) program. Population in this research were 80 suffer’s datas with 80 datas as samples, and was taken with total sampling. Results : Mother’s behavior about food during pregnancy in Dr. Pirngadi Medan General Hospital on 2017 the highest age 20-35 years old 92,5%, senior high school eduction level 67,5%, work as housewife noted 87,5%. Mother’s knowledge of food during pregnancy belong to category of good 86,2%, 13,8% belong to category of fair. Mother’s attitude of food during pregnancy belong to category of good 77,5%, 22,5 belong to category of fair. Mother’s action of food during pregnancy belong to category of good 75,5%, 25,5 belong to category of fair. Conclusion : Based on these results it was concluded that Mother’s behavior about food during pregnancy to prevent low birth weight in department obstetrics and gynecology Dr. Pirngadi Medan General Hospital on 2017 had good knowledge, good attitude about food during pregnancy. Keywords : ,